Mucus-associated microbiotas among different body sites of wild tuna from the South China Sea - Zou, Ying; Wu, Di; Wei, Lu; Xiao, Juan; Zhang, Pengfei; Huang, Hai; Zhang, Yanjie; Guo, Zhiqiang (Frontiers in Marine Science, 2023)
The mucus-associated symbionts have profound impacts on the pathogen defense, metabolism, and development of aquatic animals. To understand the microbial structure of regional endothermic fish, a total of 52 samples from the skin, oral, gill, and hindgut of wild tuna Thunnus albacares and T. obesus were determined by 16S amplicon sequencing. The results showed the diversity and composition of microbial communities varied in the four different body sites of tunas, with a greater heterogeneity between the external surface and the gut. Phyla Proteobacteria, Firmicutes, Actinobacteria and genus Acinetobacter were found in high relative abundance in all body sites. The other abundant taxa were enriched in different body sites, such as Lactobacillus and Kocuria in the skin and Geobacillus in the gut. The core taxa interacted with each other to different degrees in the four body sites, which may be related to species’ co-evolution and microbial community stability. Finally, the correlation between biomarkers and COG functions highlighted the importance of microbial biomarkers to the host. This work firstly characterized the microbial feature in different body sites of wild tunas, providing a foundational dataset to understand the microbial role in endothermic fish and to find key microbial components beneficial to farmed tunas.